Valuing the Ecosystem Services Provided by Forests In Pursat Basin, Cambodia - Rawlins, Maurice; Pagiola, Stefano; Shaad, Kashif; Alam, Mahbubul; Portela, Rosimeiry; Roy, Srabani; Vollmer, Derek; Kornexl, Werner (World Bank, Washington, DC, 2020)
The Royal Government of Cambodia (RGC) is increasingly recognizing that adequate valuation of ecosystem services is a key input to improved decision-making on protected areas, forest and natural resources more generally; but the lack of data, accepted methodologies and technical capacity have prevented it from using ecosystem valuation for decision making on meaningful scale. This analytical work is being undertaken as part of a broader effort of the World Bank to provide guidance to the RGC on managing its natural capital through landscape approaches. By focusing on the Pursat River Basin in the Cardamom Mountains, the case study presented in this report is intended to provide a practical illustration of how the ecosystem services that are provided by a forest can be valued and then compared to the benefits that would otherwise be obtained if the forest was converted to other uses. The study provides evidence of the importance of forests in providing ecosystem services that are important for Cambodia’s economy as well as for the country’s climate and disaster resilience. The results therefore intend to help the RGC quantify and communicate the value of its natural capital to Cambodia’s economy.